2010
DOI: 10.1111/j.1600-0404.2010.01380.x
|View full text |Cite
|
Sign up to set email alerts
|

Are dysautonomic and sensory symptoms present in early Parkinson’s disease?

Abstract: Parkinson's disease (PD) occurs with an annual incidence of 13/100.000, is slightly more frequent in men and is characterized by the motor symptoms tremor, rigidity, bradykinesia and postural instability. In addition, non-motor symptoms have been increasingly connected to the disease although already described in James Parkinson's 'Essay on the shaking palsy' from 1817. The motor symptoms in PD are related to the degeneration of dopaminergic cells in the substantia nigra (SN). These symptoms respond well to do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
5
0
2
Order By: Relevance
“…Evidence of pathological changes in the dorsal root ganglia and the vagus, glossopharyngeal, and internal superior laryngeal peripheral nerves is rapidly accumulating ( Mu et al., 2013a , Mu et al., 2013b ). Lewy body pathology has also been observed in the dorsal vagus ganglion and parasympathetic nuclei, enteric nervous system, and cardiac and pelvic plexus ( Wakabayashi and Takahashi, 1997 , Orimo et al., 2008 , Beach et al., 2010 , Tysnes et al., 2010 , Cersosimo and Benarroch, 2012 ). It remains to be determined whether peripheral neuron damage precipitates the development of non-motor symptoms in PD, but focused analysis on the peripheral nervous system may ultimately provide information leading to broad therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of pathological changes in the dorsal root ganglia and the vagus, glossopharyngeal, and internal superior laryngeal peripheral nerves is rapidly accumulating ( Mu et al., 2013a , Mu et al., 2013b ). Lewy body pathology has also been observed in the dorsal vagus ganglion and parasympathetic nuclei, enteric nervous system, and cardiac and pelvic plexus ( Wakabayashi and Takahashi, 1997 , Orimo et al., 2008 , Beach et al., 2010 , Tysnes et al., 2010 , Cersosimo and Benarroch, 2012 ). It remains to be determined whether peripheral neuron damage precipitates the development of non-motor symptoms in PD, but focused analysis on the peripheral nervous system may ultimately provide information leading to broad therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The most common type was presyncope (40.5%), followed by non‐specific or vague pattern (29.7%), disequilibrium (24.3%) and vertigo (5.4%). Recent studies showed that patients in even early stages of PD have dysautonomia, including orthostatic hypotension . Accordingly, it is possible that a considerable number of the present patients might have dysautonomia, including orthostatic hypotension.…”
Section: Discussionmentioning
confidence: 85%
“…They are known to be more prevalent in advanced PD, but also may occur in early stages of the disease [1,2]. Certain autonomic features, such as constipation, can precede the onset of motor symptoms [3]. A proposed six-stage pathological staging of PD suggests a predictable sequence of lesions with ascending progression from medullary or olfactory nuclei to the cortex.…”
Section: Introductionmentioning
confidence: 99%